MICRO CHEMICAL (ELEMENTAL) ANALYSIS OF LEUCAS ASPERA (WILLD) LINK EMPLOYING SEM-EDAX (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The plant, Leucas aspera (Willd) Link is well known for its varied medicinal uses. Present study deals with its micro chemical (elemental) characterization using Energy Dispersive X-ray Analysis (EDAX) detector fitted to Scanning Electron Microscope. The plant has very interesting morphology. Crystals of varied shape and inclusions/exudates were noticed within and on the leaf & stem surfaces. Various plant parts analysed were, stem surface, stem sections, stem inclusions, blebs on stem hairs, crystals of varied shape, root sections, abaxial and adaxial surfaces, flower, seed and seed caruncle. Lot of variation in elemental composition was observed in various plant parts. Major elements detected were Carbon, Oxygen, Calcium, Silica, and Aluminum. Other elements found were Iron, Sodium, potassium, Phosphorus and Chlorine.